"BOBURNOMA" IS THE PRIMARY SOURCE FOR DESCRIBING NATURE. (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
ABSTRACT This article is about the heritage of Zahiruddin Muhammad Babur'smasterpiece "Baburnoma". In the work, Babur gives detailed information about hisorigin, military campaigns, and the great kingdom he founded in India. Although"Boburnoma" contains many names of people and places, they are interesting and easy to read. Babur, being a great statesman, as a naturalist and tourist scientist, observed and covered events so carefully that many of them completely correspond to the conclusions of today's science. The work contains detailed and sufficient information about the nature, appearance, benefits and harms of rivers, mountains, deserts, cities, villages, cities, fields and steppes that Babur visited. This priceless legacy of Zahiruddin Muhammad Babur is a unique truth that leads our history forward into the future. That is why the work of this great thinker is still being repeatedly studied by orientalists. In 1980, UNESCO announced a competition for a new French translation.